Efficacy, safety, and lot-to-lot immunogenicity of an inactivated SARS-CoV-2 vaccine (BBV152): interim results of a randomised, double-blind, controlled, phase 3 trial. Issue 10317 (11th December 2021) - Ella, Raches; Reddy, Siddarth; Blackwelder, William; Potdar, Varsha; Yadav, Pragya; Sarangi, Vamshi; Aileni, Vinay K; Kanungo, Suman; Rai, Sanjay; Reddy, Prabhakar; Verma, Savita; Singh, Chandramani; et al.
Summary: Background: We report the clinical efficacy against COVID-19 infection of BBV152, a whole virion inactivated SARS-CoV-2 vaccine formulated with a toll-like receptor 7/8 agonist molecule adsorbed to alum (Algel-IMDG) in Indian adults. Methods: We did a randomised, double-blind, placebo-controlled, multicentre, phase 3 clinical trial in 25 Indian hospitals or medical clinics to evaluate the efficacy, safety, and immunological lot consistency of BBV152. Adults (age ≥18 years) who were healthy or had stable chronic medical conditions (not an immunocompromising condition or requiring treatment with immunosuppressive therapy) were randomised 1:1 with a computer-generated randomisation scheme (stratified for the presence or absence of chronic conditions) to receive two intramuscular doses of vaccine or placebo administered 4 weeks apart. Participants, investigators, study coordinators, study-related personnel, the sponsor, and nurses who administered the vaccines were masked to treatment group allocation; an unmasked contract research organisation and a masked expert adjudication panel assessed outcomes. The primary outcome was the efficacy of the BBV152 vaccine in preventing a first occurrence of laboratory-confirmed (RT-PCR-positive) symptomatic COVID-19 (any severity), occurring at least 14 days after the second dose in the per-protocol population. We also assessed safety and reactogenicity throughout the duration of the study in all participants who had received at least one dose of vaccine or placebo. This report contains interim results (data cutoff May 17, 2021) regarding immunogenicity and safety outcomes (captured on days 0 to 56) and efficacy results with a median of 99 days for the study population. The trial was registered on the Indian Clinical Trials Registry India, CTRI/2020/11/028976, and ClinicalTrials.gov, NCT04641481 (active, not recruiting). Findings: Between Nov 16, 2020, and Jan 7, 2021, we recruited 25 798 participants who were randomly assigned to receive BBV152 or placebo; 24 419 received two doses of BBV152 (n=12 221) or placebo (n=12 198). Efficacy analysis was dependent on having 130 cases of symptomatic COVID-19, which occurred when 16 973 initially seronegative participants had at least 14 days follow-up after the second dose. 24 (0·3%) cases occurred among 8471 vaccine recipients and 106 (1·2%) among 8502 placebo recipients, giving an overall estimated vaccine efficacy of 77·8% (95% CI 65·2–86·4). In the safety population (n=25 753), 5959 adverse events occurred in 3194 participants. BBV152 was well tolerated; the same proportion of participants reported adverse events in the vaccine group (1597 [12·4%] of 12 879) and placebo group (1597 [12·4%] of 12 874), with no clinically significant differences in the distributions of solicited, unsolicited, or serious adverse events between the groups, and no cases of anaphylaxis or vaccine-related deaths. Interpretation: BBV152 was highly efficacious against laboratory-confirmed symptomatic COVID-19 disease in adults. Vaccination was well tolerated with no safety concerns raised in this interim analysis. Funding: Bharat Biotech International and Indian Council of Medical Research.